Price De-Capping of Milk and Meat in Punjab, Pakistan: Social and Economic Implications - Waheed, Muhammad Ahsan (Journal of Pakistan Administration, 2021)
The research should be considered as an introductory case study based upon review of selected literature, field observations and participant interviews to highlight the importance of de-capping of the prices of meat and milk in Pakistan and to discuss the implications of the decision for the livestock sector, food security and economy of Pakistan. Livestock, a sub-sector of agriculture, provides us with meat and milk which are essential components of human diet. Human beings obtain 34 percent of protein and 18 percent of dietary energy from meat and milk. Livestock sector has the potential to play a vital role in economic development, food security and rural socio-economic uplift of the country.